Defined Daily Dose and Appropriateness of Clinical Application: The Coxibs and Traditional Nonsteroidal Anti-Inflammatory Drugs for Postoperative Orthopaedics Pain Control in a Private Hospital in Malaysia - Faizah Safina Bakrin; Mohd Makmor-Bakry; Wan Hazmy Che Hon; Shafeeq Mohd Faizal; Mohamed Mansor Manan; Long Chiau Ming (MDPI AG, 2020)
Introduction: Drug utilization of analgesics in a private healthcare setting is useful to examine their prescribing patterns, especially the newer injectable cyclooxygenase (COX)-2 inhibitors (coxibs). Objectives: To evaluate the utilization of coxibs and traditional nonsteroidal anti-inflammatory drugs (tNSAIDs) indicated for postoperative orthopaedic pain control using defined daily dose (DDD) and ratio of use density to use rate (UD/UR). Method: A retrospective drug utilization review (DUR) of nonsteroidal anti-inflammatory drugs (NSAIDs) at an inpatient department of a private teaching hospital in Seremban, Malaysia was conducted. Patients' demographic characteristics, medications prescribed, clinical lab results, visual analogue scale (VAS) pain scores and length of hospital stay were documented. Orthopaedic surgeries, namely arthroscopy, reconstructive, and fracture fixation, were included. Stratified random sampling was used to select patients. Data were collected through patients' medical records. The DDD per 100 admissions and the indicator UD/UR were calculated with the World Health Organization's DDD as a benchmark. The inclusion criteria were patients undergoing orthopaedic surgery prescribed with coxibs (celecoxib capsules, etoricoxib tablets, parecoxib injections) and tNSAIDs (dexketoprofen injections, diclofenac sodium tablets). Data were analysed descriptively. This research was approved by the academic institution and the hospital research ethics committee. Result: A total of 195 records of patients who received NSAIDs were randomly selected among 1169 cases. In term of the types of orthopaedic surgery, the ratio of included records for arthroscopy:fracture fixation:reconstructive surgery was 55.4:35.9:8.7. Most of the inpatients had low rates of common comorbidities such as cardiovascular disease as supported by their baseline parameters. The majority were not prescribed with other concomitant prescriptions that could cause drug interaction (74.9%), or gastroprotective agents (77.4%). Overall, DDDs per 100 admissions for all NSAIDs were less than 100, except for parecoxib injections (389.23). The UD/UR for all NSAIDs were less than 100, except for etoricoxib tablets (105.75) and parecoxib injections (108.00). Discussion: As per guidelines, the majority (96.9%) received other analgesics to ensure a multimodal approach was carried out to control pain. From the UD/UR results, the arthroscopy surgery was probably the most appropriate in terms of NSAID utilization. Conclusion: The prescribing pattern of NSAIDs except parecoxib was appropriate based on adverse effect and concurrent medication profile. The findings of this DUR provide insight for a low-risk patient population at a private specialized teaching hospital on the recommended use of NSAIDs for postoperative orthopaedic pain control.